Learning Management System – Berbasis Blended Learning sebagai Alternatif Pembelajaran Biologi untuk Meningkatkan Keterampilan Kolaborasi Siswa - Andi Nurul Adha Andika; Adnan; Asham Bin Jamaluddin (Biosfer: Jurnal Pendidikan Biologi, 2026)
This study aims to determine the effect of various types of blended learning (station rotation, lab rotation, and pedati) on collaboration skills. The research design used a quasi-experimental approach. The population in this study included all eighth-grade students at SMP Negeri 2 Sengkang, with the research sample consisting of classes VIII.1, VIII.2, VIII.3, and VIII.4. In the implementation, the experimental classes were taught using station rotation, lab rotation, and pedati types of blended learning, while the control classes were taught using STAD. The research instrument used a collaboration skills observation sheet based on five indicators: Responsibility, Respect, Contribution, Organize Work, and Work as a Whole Team. Data collection was conducted by an observer before and after the treatment. Data analysis techniques used Ancova with a significance level of 0.05. The results of the study indicate that there is an effect of blended learning types station rotation, lab rotation, and pedati on collaboration skills. Based on the LSD (Least Significant Difference) post-hoc test, the station rotation type of blended learning showed the highest average in collaboration skills compared to the other types. The findings of this study indicate that blended learning can be applied in classroom learning to support the development of students' collaborative skills in facing educational challenges in the digital era.